What is Europe? A Reflection from Overseas on the Federalization of the European Union - Vanney, María Alejandra (PRAWO i WIĘŹ, 2025)
This paper explores the continent’s identity through four foundational pillars — logos, ethos, polis, and ius — that have shaped both European and Western civilization. Amidst the richness of its diversity, Christianity, understood as a historical and cultural cornerstone rather than a confessional framework, emerges as a potential unifying force. However, as the European Union shifts towards an economistic and procedural approach, prioritizing regulations over deeper philosophical foundations, its claim to be a “union of values” risks becoming merely declarative. In this context, reconsidering the nature of European unity becomes essential. Rather than seeking homogenization or a superficial consensus, Europe’s identity should embrace the paradox of unity in diversity — an intricate interplay of cultural, historical, and moral traditions that fosters dynamism and innovation. Moreover, the course of EU integration, whether in a federal or alternative form, has profound implications not only for Europe itself, but also for the wider Western world and its moral and political foundations.